Defusing contested authority: EU energy efficiency policymaking. Issue 1 (2nd January 2020) - Dupont, Claire
ABSTRACT: EU energy efficiency policymaking has faced repeated contestation. Such contestation has been both sovereignty-based, when member states contest the EU's authority to make policy on energy efficiency (subsidiarity claims), and substance-based, when concerns are raised about the choice or ambition of a policy measure. Yet, energy efficiency has become one of the five dimensions of the Energy Union. It is thus an example of EU policymaking advancing even under contestation. I investigate three main strategies to manage these contestations: (1) framing and reframing energy efficiency to enhance and consolidate authority at EU-level and to mitigate contestations over this authority; (2) developing the legal framework; and (3) applying flexibility in policy measures and employing mixed soft and hard governance tools. These strategies are employed, and interact, over both a 'long game' and a 'short game'.